2D Ising Model for Adsorption‐induced Enantiopurification of Racemates. Issue 2 (18th December 2020) - Dutta, Soham; Yun, Yongju; Widom, Michael; Gellman, Andrew J.
Abstract: Mechanisms for the spontaneous transformation of achiral chemical systems into states of enantiomeric purity have important ramifications in modern pharmacology and potential relevance to the origins of homochirality in life on Earth. Such mechanisms for enantiopurification are needed for production of chiral pharmaceuticals and other bioactive compounds. Previously proposed chemical mechanisms leading from achiral systems to near homochirality are initiated by a symmetry‐breaking step resulting in a minor excess of one enantiomer via statistical fluctuations in enantiomer concentrations. Subsequent irreversible processes then amplify the majority enantiomer concentration while simultaneously suppressing minority enantiomer production. Herein, equilibrium adsorption of amino acid enantiomer mixtures onto chiral and achiral surfaces reveals amplification of surface enantiomeric excess relative to the gas phase; i. e. enantiopurification of chiral adsorbates by adsorption. This adsorption‐induced amplification of enantiomeric excess is shown to be well‐describe by the 2D Ising model. More importantly, the 2D‐Ising model predicts formation of homochiral monolayers from adsorption of racemic mixtures or prochiral molecules on achiral surfaces; i. e. enantiopurification with no apparent chiral driving force. Abstract : Enantiopurification by adsorption : Auto‐amplification of enantiomeric excess has been observed during the adsorption of amino acid enantiomer mixtures from the gas phase onto chiral and achiral Cu single crystal surfaces; i. e. ee s >ee g . This phenomenon is predicted by the 2D‐Ising model which can be used to simulate and reproduce the observed behavior. The most interesting prediction of the 2D Ising model is that at low temperatures, enantiomeric purity of adsorbates can be achieved during adsorption from racemic mixtures or by prochiral compounds adsorbing onto achiral surfaces.